Global-Service Learning and Student-Athletes: A Model for Enhanced Academic Inclusion at the University of Washington - Holly M. Barker (Ubiquity Press, 2017)
Background The University of Washington (UW) continues to create opportunities to engage all students in transformational undergraduate educational opportunities, such as study abroad. Objective This article describes specific efforts to increase inclusion for student-athletes in study abroad, particularly for first-generation students, including low-income students of color. Given the overrepresentation of students of color in sports vis-à-vis the larger student body at predominantly white institutions (PWIs), like UW, service-learning in communities beyond campus boundaries provides opportunities to apply international learning to a local context and to create a continuum of learning. Methods By coupling educational theories from the classroom-particularly theories related to power and privilege-with community-based leadership in local communities, students are better prepared to actively engage in improving their own institutions. During the summers of 2013, 2014, and 2015, the author was the instructor for study abroad courses to French Polynesia with student-athletes. The courses were for 12 days (10 days on the ground and 2 days of flying), the maximum time that football players could be away from required summer workouts. This paper examines student evaluations from the French Polynesia trip in 2015. Findings Student-athlete evaluations of a study abroad experience underscored: the transformative impact of study abroad to their academic, social, and athletic lives; the benefit of creating family-like relationships outside the confines of their sport; an appreciation for the many forms where indigenous knowledge resides, such as in navigation, dance, fishing, weaving, and cooking; intense feelings of culture shock upon return to the US, even when the trip is short in duration; a desire to engage with the diverse communities in Seattle beyond the scope of the program's structure, and; frustration, particularly for the male student-athletes, about the ways coaches, family, and friends wanted to frame the study abroad experience as a tourist experience in the South Pacific. In this regard, the student-athletes encountered stereotypes from their own communities that framed Oceania as a place for tourism, and student-athletes as uninterested in deep engagement with research and theory-stereotypes that the student-athletes resist. Conclusions This paper explains how the findings, coupled with Hartman and Kiely's theories for global service learning (GSL), lead to recommendations for strengthening the future connections between global and local learning for students.